The Effect of Active and Receptive Musical Training on Emotional Memory in Preschoolers - Benitez, Maria Angelica (2023)
Music training has beneficial effects on the development of various skills in children, whether it is receptive (listening to music) or active (producing music). Although it is known that emotional items are better remembered than neutral ones, this phenomenon remains poorly understood in preschoolers. This study aimed to evaluate the effect of music training on the emotional memory of 4- and 5-year-old preschool children. One hundred and forty-eight preschool children from two private kindergartens in Buenos Aires, Argentina, were randomly divided into groups to receive either active or receptive music training. The content was adapted from the educational music curriculum or regular music classes over a period of 4 weeks. Next, they observed 24 neutral and emotional pictures, rated their valence and arousal, and their recall and recognition (immediate and deferred) were assessed. The data was analyzed using a repeated measures analysis of variance (ANOVA). The between factors were conditions (control versus active versus receptive) and age (4 and 5), while picture (neutral, positive, or negative) was the repeated measure. The primary findings indicated that children exposed to music training had better mnemonic performance than the control group and they remembered more emotional than neutral images. These results highlight the relevance of music programs in school curricula.